The role of economic conditions on the effectiveness of Greek humorous TV advertising - Zotos, Yorgos; Boutsouki, Christina; Hatzithomas, Leonidas (My University, 2014)
Based on an experimental study in Greece, the present paper aims to investigate the effectiveness of humorous TV commercials in recessionary and expansionary periods. The findings challenge the intuitive belief among practitioners that humor provides an advantageous type of advertising message in recessions. Humorous commercials not only did they not create more positive attitude toward the ad in recessions compared to expansions, but they also generated less favorable attitudes toward the ad during the austere Greek recession.
Keywords: Humorous TV commercials; Advertising message in recessions; Economic Conditions